2012
DOI: 10.1155/2012/543230
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Soybean Oil Solvent Extraction through Enzymatic Pretreatment

Abstract: The purpose of this study is to evaluate multienzyme hydrolysis as a pretreatment option to improve soybean oil solvent extraction and its eventual adaptation to conventional processes. Enzymatic action causes the degradation of the cell structures that contain oil. Improvements in terms of extraction, yield, and extraction rate are expected to be achieved. Soybean flakes and collets were used as materials and hexane was used as a solvent. Temperature, pH, and incubation time were optimized and diffusion coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The utilization of enzymatic pretreatment prior to solvent extraction can be attributed to the degradation of cellulose, pectin and protein, destroying the structural integrity of the seed cell wall and liberating more oils 47) . F R Mohamed revealed that enzymatic hydrolysis of goldenberry pomace oil followed by n-hexane extraction can shorten the extraction time and improve extraction efficiency 48) .…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of enzymatic pretreatment prior to solvent extraction can be attributed to the degradation of cellulose, pectin and protein, destroying the structural integrity of the seed cell wall and liberating more oils 47) . F R Mohamed revealed that enzymatic hydrolysis of goldenberry pomace oil followed by n-hexane extraction can shorten the extraction time and improve extraction efficiency 48) .…”
Section: Discussionmentioning
confidence: 99%
“…Mass transfer is the process of mass transfer on the surface of particles and diffusion inside (Bandura et al, 2021). Recent studies on the improvement of extraction processes that can reduce the amount of energy consumed, use harmless alternative solvents, and ensure the production of a safe, benign extract product and the feasibility of using microwave technology are reported by the authors (Grasso et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This aims to damage the cell wall (lignocellulose) so that the results of oil extraction will be maximized because the accessibility of the solvent into the analyte will be greater [7,8]. Pretreatment has been shown to increase the yield of oil extraction, for example in the extraction of castor oil [9], tomatoes [10], soybeans [11], and cumin [12]. Cell wall destruction can be done mechanically and non-mechanically.…”
Section: Introductionmentioning
confidence: 99%